La enseñanza del derecho internacional de los derechos humanos: una revisión del libro de texto - Binder, Christina (2021)
The increased focus on, and incorporation of, human rights into university curricula have led to a significant number of recently published (international) human rights textbooks. In a field that is distinctly known for idealism, human rights textbooks are the first introduction for students to the international human rights framework. With varying focus, methodology, tool sets and depth of engagement with a topic, there is a broad variety available on the market from which to choose. This review offers a selection of human rights textbooks that represent different writing styles and meet different teaching needs and preferences